Clinical and Pathological Features of Childhood-Onset Nemaline Myopathy: A Report of Four Cases - Chao Jiang; Jianping Wang; Haidong Lu (Case Reports in Medicine)
We examined whether immunological abnormalities can be found in the specimens of four childhood-onset nemaline myopathy (NM) patients without autoimmune diseases. Pathological examination revealed that nemaline rods were found in all specimens. The immunohistochemical results showed that CD4 positive cells and some other cells were gathered among the necrotic muscle fibers. We conclude that immunological abnormalities are present in the specimens of certain childhood-onset NM patients without autoimmune diseases. Further evaluation of the immunological changes is warranted in childhood-onset NM patients.